Kurikulum Pendidikan Guru: Metode Simulasi dalam - Hasbullah Hasbullah (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
The use of teaching methods based on the formation of students' abilities, such as having creativity. Each teaching method has advantages and disadvantages so that it can be taken into consideration in choosing the method. The weaknesses of the method must be anticipated and reviewed by the teacher so that its use can be effective. Simulation learning method can be used as a teaching method with the assumption that not all learning processes can be carried out directly on the actual object. Likewise, to develop an understanding and appreciation of an event that leads more to psychomotor, the use of a simulation learning model will be very useful.